Annals of pediatric cardiology (MedKnow Publications, 2008)
The Annals of Pediatric Cardiology is being launched with the idea of providing a common platform for presenting data and expressing views for members of the following specialties viz. cardiology, cardiac surgery, anesthesiology, intensive care as well as more basic disciplines of pathology, molecular biology and genetics. We would also like this journal to be a medium for discussing related issues like medical education, paramedical training, healthcare costs, human resources, medical practices in economically challenged countries, ethics in medicine and so on. We plan to publish a teaching series on clinico-morphological correlation and hemodynamic rounds for post graduates and fellows in Pediatric Cardiology.